Depression and Cognitive Dissonance: an empirical exploration of a close relationship - De Vries, Jan; Higgins, Agnes (My University, 2023)
This qualitative study seeks to establish whether dissonance theory provides a meaningful avenue to add insights into the experience of depression. Semi-structured interviews were used (n=30) in which fifteen participants with a diagnosis of depression (DD) were compared with an equal size group with no experience of depression (ND). Responses to a depression scale (CESD-10) confirmed a significant difference in depression scores between groups. The interviews were analyzed using template analysis. Findings showed that in comparison with the non-depressed group, participants with depression reported more incisive dissonance inducing life events, more prolonged unresolved dissonance, less variation in cognitive efforts to reduce dissonance, and more rumination. It was concluded that dissonance theory provides an explanatory model for depression experiences and could inform further development of interventions. With little research reported to date, both quantitative and qualitative research are needed.
Keywords: Mental health promotion; cognitive dissonance